Stakeholders management in public hospitals in the context of resources = Zarządzanie interesariuszami w szpitalach publicznych - od zarządzania do relacji z interesariuszami - Austen, Agata (Zielona Góra: Faculty of Economics and Management Press)
Public sector organisations have a sufficient influence to win political legitimization and resources to finance their operations by satisfying their stakeholders. Organizations that adopt stakeholder management principles probably better satisfy their constituent needs and balance their interests, which results in higher capacity of goal achievement.
Keywords: interesariusze; zasoby; ochrona zdrowia; stakeholders; resources; healthcare